Uprość wyrażenia
a⁻²:a⁻⁴*a=

a⁻⁷*b⁻³*b*a²=

x⁻²:x⁻⁴=

a⁻⁷:a⁻⁹=

(a⁻⁴)⁴:(a³)⁻⁸=

4,5⁰+2*(½)⁻¹+3(⅓)⁻²=

4,8:(-2)³-4*(-1,5)⁻²=

1,5*(-0,5)²-2,5:(½)⁻²=

Oblicz:
(-3,5)⁻²=
(-12)⁻²=
(4,7)⁻²=
-13⁻²
(4⅓)⁻¹=
(-0,25)⁻¹=
-2,5⁻³=

(5,8)⁰=
(⅔)³=
(4⅓)²=
-1,5*(⅓)²=
-12:(⅔)²=
4²*(½)³=

√9/25=
√49/64=
2⅓:(-1,5)=
-4⅓:(-1,3)=
5,5-4/5:2=
(⅔)⁴*(¾)⁴=
(⅔)⁹:(⅔)⁷=
[(⅔)³*(⅔)⁷]:(⅔)⁸=

1

Odpowiedzi

  • Użytkownik Zadane
2009-08-20T22:00:03+02:00
A⁻²:a⁻⁴*a= a³
a⁻⁷*b⁻³*b*a²=a⁻⁸
x⁻²:x⁻⁴= x²
a⁻⁷:a⁻⁹=a²
(a⁻⁴)⁴:(a³)⁻⁸=a⁸
4,5⁰+2*(½)⁻¹+3(⅓)⁻²=1+4+27=32
4,8:(-2)³-4*(-1,5)⁻²=0,6-16/9=-53/45
1,5*(-0,5)²-2,5:(½)⁻²=0,375-10=-9,625

(-3,5)⁻²=4/49
(-12)⁻²=1/144
(4,7)⁻²=100/2209
-13⁻²= - 1/169
(4⅓)⁻¹=3/13
(-0,25)⁻¹=-4
-2,5⁻³=-8/125

(5,8)⁰=1
(⅔)³=8/27
(4⅓)²=169/9
-1,5*(⅓)²=-1/6
-12:(⅔)²=-27
4²*(½)³=16*1/8=2

√9/25=√3/5
√49/64=√7/8
2⅓:(-1,5)=-14/9
-4⅓:(-1,3)=10/3
5,5-4/5:2=5,1
(⅔)⁴*(¾)⁴=1/16
(⅔)⁹:(⅔)⁷=4/9
[(⅔)³*(⅔)⁷]:(⅔)⁸= 4/9